THE LACK OF MEMORY ABOUT MULTICULTURALISM IN THE LITERATURE ON THE SETTLEMENT TO THE WESTERN LANDS OF POLAND - Gieba, Kamila (Porównania, 2018)
The article is about the Polish literature on resettlements to the so-called Regained Territories. The postwar resettlement was the result of voluntary and enforced migrations – the aftermath of the shift of Polish territorial borders in 1945. The migrants were to be a homogeneous society, thus writers tended to avoid negative representations of a cultural melting pot. The article presents selected areas that have been marginalized in the collective memory: the separateness of the residents of Kresy, the conflicts in the communities of migrants and the autonomy of ethnic groups.